An analysis of the ACS / Dragados merger - Torrado, Diogo Nuno Correia (2008)
This dissertation analyses the merger between ACS, Actividades de Construcción y Servicios, S.A. (“ACS”) and Dragados, S.A. (“Dragados”), which occurred between 2002 and 2003. ACS, one of the leading construction companies in Spain, growing through acquisitions since mid 1980’s, acquired in April 19, 2002, Santander Central Hispano’s stake in the competitor Dragados (23.5% of share capital). In the following year, ACS acquired, in the market, another 10% of Dragados share capital (as of March 21, 2003) and, later in that year (as of December 15, 2003), a merger between the two companies was completed and full integration was initiated. This dissertation characterizes both companies, goes through the mains events of the merger process, looks at the operation rationale, and tries to determine if the premiums paid by ACS versus Dragados’ closing price at (i) the date of Santander Central Hispano stake acquisition (59% premium), (ii) nine months later, at the date of the acquisition of the further 10% (36% premium) and (iii) implicit in the final merger conditions (1% premium) were, as of December 2003, positively outbalanced with stock price evolution until the merger was concluded and with future synergies to be achieved after full integration of the two companies. The final outcome is that, as of December 31, 2003, the merger had a strong rationale and, despite the referred premiums paid by ACS, globally created value to ACS shareholders, mainly due to both stock price evolution and the future synergies to be achieved: tax savings on goodwill amortization, headcount reduction and economies of scale in cost structure. Also, I present a brief event study to show that Dragados shareholders benefited from positive speculative movements around the target stock price at the day of the first acquisition announcement (April 19, 2002). Final Note – This dissertation contains information and forward-looking statements of the time of the merger process, with respect to ACS, Dragados and to ACS / Dragados new group (“New ACS”) compiled from different sources. Therefore, market evolution of both companies and actual results may differ materially from the information and results presented in this dissertation.